(untitled) (Harmoni, 2015)
This study employs the analytical descriptive research that explores in-depth information about the existence of BahaΓÇÖi religion in Indonesia that many societies have not known about it. The study describes phenomenon and facts about BahaΓÇÖi religion. The data collection consists of literature study, document analysis, in-depth interview, and observation. The study that is conducted in Cebolek village, Margoyoso district, Pati aims to know the BahaΓÇÖi history, main teachings, and adherents as well their spread; find the implementation of government policy to fulfill BahaΓÇÖi adherentsΓÇÖ right; to figure out the social relationship between BahaΓÇÖi adherents and their society around them. The results of study show that BahaΓÇÖi quite exists in Cebolek village, Margoyoso district, Pati even though it has not developed, less than 23 people; BahaΓÇÖi adherents have their rights in obtaining services though in fact there are some changes; their social relationship with their society is good because they behave politely and they are active in some activities in their social environment.